Simulasi SIR Kecanduan Media Sosial Mahasiswa FMIPA UNRAM dengan Metode Euler dan Heun - Lestari, Natasya Dyahayu; Arimanda, Abi Rizka Yulia; Nisa, Gina Agisna (JSN : Jurnal Sains Natural, 2025)
Social media has become an important part of daily life, especially among university students. The ease of access to information and communication through digital platforms brings both positive and negative impacts, one of which is the increasing addiction to social media. This study aims to analyze social media addiction among students using the SIR (Susceptible-Infected-Recovered) model. This model categorizes the population into three groups: individuals susceptible to addiction ( ), individuals experiencing addiction ( ), and individuals who have recovered from addiction ( ). The model is solved using numerical methods, namely the Euler method and the Heun method, which are applied in simulations using MATLAB software. The simulation results show that social media addiction spreads within a population following a distinctive pattern, where the number of addicted individuals increases before eventually declining due to increased awareness and specific interventions. Additionally, the Heun method provides more accurate solutions compared to the Euler method, highlighting the importance of precise numerical approaches in modeling addiction dynamics. These findings offer insights into how social media addiction develops and how prevention and recovery strategies can be effectively implemented among students.